Medical Costs of Fatal and Nonfatal Falls in Older Adults - Florence, Curtis S.; Bergen, Gwen; Atherly, Adam; Burns, Elizabeth; Stevens, Judy; Drake, Cynthia (Journal of the American Geriatrics Society (JAGS), 2018)
Objectives To estimate medical expenditures attributable to older adult falls using a methodology that can be updated annually to track these expenditures over time. Design Population data from the National Vital Statistics System (NVSS) and cost estimates from the Web‐based Injury Statistics Query and Reporting System (WISQARS) for fatal falls, quasi‐experimental regression analysis of data from the Medicare Current Beneficiaries Survey (MCBS) for nonfatal falls. Setting U.S. population aged 65 and older during 2015. Participants Fatal falls from the 2015 NVSS (N=28,486); respondents to the 2011 MCBS (N=3,460). Measurements Total spending attributable to older adult falls in the United States in 2015, in dollars. Results In 2015, the estimated medical costs attributable to fatal and nonfatal falls was approximately $50.0 billion. For nonfatal falls, Medicare paid approximately $28.9 billion, Medicaid $8.7 billion, and private and other payers $12.0 billion. Overall medical spending for fatal falls was estimated to be $754 million. Conclusion Older adult falls result in substantial medical costs. Measuring medical costs attributable to falls will provide vital information about the magnitude of the problem and the potential financial effect of effective prevention strategies.